The propensity of fomite spread of SARS-CoV-2 virus through produce supply chain - Adedeji, Akinbode A. (2023)
A direct quote from CDC’s Web site dated April 2021 reads, “It is possible for people to be infected (with SARS-CoV-2) through contact with contaminated surfaces or objects (fomites), but the risk is generally considered to be low.” How low the risk is, we do not know yet because there are no enough evidence-based empirical studies to support or counter this claim. Here is what we know, SAR-CoV-2, the virus that causes COVD-19 continues to pose a serious threat and has caused significant disruption to human activities, including food production since it became a pandemic in 2020. As of June 2022, 192 countries/regions have reported at least one case of the virus infection, and over 535 million cases have been reported globally (that is 294 million more since October 2021) with 85.5 million of those in the USA alone. Over 6.3 million people have died (more than a million in the USA alone as of June 2022) from the virus infection worldwide, with 42,039 deaths alone in the last 28 days (as of June 13, 2022).